ANALISIS PROGRAM PEMBERDAYAAN DESA (PPD) DALAM PENERAPAN EKONOMI MIKRO ISLAM DI DESA TALANG PADANG - Sela Lestari; Muhammad Iqbal Fasa; Suharto Suharto (LP2M Universitas Bina Bangsa, 2022)
This paper argues that village development is a more inclusive implementation of development. Village development requires a process that prioritizes synchronization between sectors and actors and prioritizes innovation. One of the paradigms that is quite present in development theory is the paradigm of developmentalism. Using the paradigm of developmentalism, this paper intends to map the development carried out through infrastructure development so that development in the village becomes more inclusive. Development planning approach that includes planning, direction, motivation, communication (Rohma, 2021), as well as directing implementation. This paper is compiled using qualitative methods aimed at answering how village development through infrastructure can support the development of more inclusive villages